ASSESSING THE ECONOMIC PROFITABILITY OF FOODGRAIN CULTIVATION IN SANGLI DISTRICT - Kombde, S.T.; Mohite, Rupali Vasant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The study investigated the foodgrain production, cultivator’s income and profitability derived from foodgrain cultivation in Sangli District. Primary data obtained from 20 villages and 384 respondents in 2021 which allowed to assess the cultivation area as well as productivity and economic returns from Rice, Wheat, Bajara, and Jowar. Rice proves the most financially profitable crop for farmers of the Sangli district because it generated the highest income per hectare. Statistics inferences shows that rice cultivation produces 50.41 quintals of yield per hectare which exceeds all other selected foodgrains. The Jowar delivers the maximum gross monetary income per hectare at Rs. 143039 followed by Bajra (Rs. 138150) then Rice (Rs. 119468) and finally wheat (Rs. 117,121). Rice stands as the most financially profitable crop because it offers the highest benefit-cost ratio (1.69) when compared to wheat (1.48) and bajara (1.35) and jowar (1.30). Results from the study demonstrated major distinctions between cultivation cost and income across all the selected foodgrain crops. Better financial assistance coupled with technological innovation and efficient machinery are essential to improve productivity and profitability of foodgrain in study region. Strategic government policies are needed to stabilize cultivation costs and enhance farmer income in Sangli District.